Sistem Ekonomi Koperasi Sebagai Solusi Masalah Perekonomian Di Indonesia - Thobby Wakarmamu; Christine Marina Wakarmamu (Jurnal Kajian Ekonomi dan Studi Pembangunan, 2015)
Until now, it is unclear what the economic system adopted by Indonesian nation. Perhaps people say economic system Indonesia is a mix between the capitalist economic system and the Socialist-Liberal-Command. Whatever the Indonesian economic system adopted, a clear until now the Indonesian economy increasingly lagging behind countries - countries ASEAN others who used it under Indonesia. Indonesia's economy is still not in favor of interest people. The little people are likely still not optimal in enjoy the fruits of national development, resulting in a gap that is very width between the rich and the poor. Since the State of Indonesia's independence, actually Bung Hatta launched a cooperative economic system for the Indonesian nation. Even This cooperative economic system has been set forth in the Constitution 'of 1945, in particular Article 33. But in reality, the government (nation) Indonesia never consistent with Article 33 is in the running wheel the national economy. Perhaps this is what causes the economy Indonesia continues to face chronic problems such as those in on. If the economic system is fundamentally cooperative studied, actually cooperative has characteristics that are closely aligned with the situation and culture Indonesian nation. Therefore, it is not something that is not possible if the cooperative economic system serve as a solution to Indonesia's economic problems. The issue is whether the government and the Indonesian people can apply cooperative economic system This consequently and continue. Keywords :  Cooperative Economic System, Indonesia Economy